Carbonation of steel slag and gypsum for building materials and associated reaction mechanisms. (November 2019) - Wang, Xue; Ni, Wen; Li, Jiajie; Zhang, Siqi; Hitch, Michael; Pascual, Rodrigo
Abstract: The carbonation of steel slag to produce building material is a useful way to increase the utilization of steel slag and absorb carbon dioxide. In this study, gypsum, steel slag, and water were mixed, compaction-shaped, and carbonation-cured as a means of improving the strength of the steel slag. It was observed that gypsum promoted an increase in both the compressive strength and the CO2 uptake of steel slag. CO2 uptake was positively correlated with strength. Microanalysis indicated that the main hydration product were C-S-H phases and ettringite, while the main carbonation products were calcite and monocarbonate (C3 A. CaCO3 .11H2 O). Gypsum is speculated to promote the rapid hydration of steel slag to form ettringite (C3 A.3CaSO4 .32H2 O), which then reacts with CO2 to produce monocarbonate; thus, gypsum plays a catalytic role in this system. The results of this study therefore provide theoretical guidance for the preparation of steel slag–gypsum carbide building materials.